Hubungan Dukungan Suami, Usia Ibu, Dan Gravida Terhadap Kejadian Emesis Gravidarum - Mariantari1, Yunia -; Lestari, Widia -; -, Arneliwati - (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2014)
The aim of this research was to identify the correlation between husband support, mother’s age, and gravida with the incidence of emesis gravidarum in Puskesmas Harapan Raya Pekanbaru. The research used correlation descriptive method with cross sectional approach. The sampling technique explored purposive sampling with 38 respondents which were selected based on inclusion criteria. Data collection tool in this research was a questionnaire which have been tested for it’s validity and reliability. The data were analyzed by using Chi Square test. The results showed that the percentage of respondents with emesis gravidarum who had lower of husband support was 88,9%, mother age <20 and >35 years was 90,0%, and primigravida was 86,4%. It can be concluded that there were no relationship between husband support (p value < 0,05), and gravida (p value = 0,03) with the incidence of emesis gravidarum and there was no relationship between mother’s age (p value = 0,23) with the incidence of emesis gravidarum. Based on the result of this study, it recommended to health provider for giving more health promotion about antenatal period that involved the husband in antenatal class in order to support their wife. Keyword: emesis gravidarum, gravida, husband support, mother’s age